Cubic boron nitride polycrystal and method for producing same
By treating the hexagonal crystal boron nitride raw material under high pressure, forming a fine-grained, coarse-grained and layered cubic crystal boron nitride polycrystalline hybrid structure, the problem of insufficient material hardness and Young's modulus in the prior art is solved, and the problem of insufficient material hardness and Young's modulus is realized. It has high hardness and high Young's modulus cubic boron nitride polycrystalline suitable for high-precision cutting and grinding tools.
Patent Information
- Application Number
- CN202410646126.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-22
- Filing Date
- 2024-05-23
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-05-23
AI Technical Summary
Existing cutting tools and grinding tools are prone to elastic deformation during processing, resulting in reduced processing accuracy. The Young's modulus of existing cubic boron nitride polycrystals is insufficient, making it difficult to meet the requirements of high hardness and high elastic deformation resistance. .
By heating the hexagonal boron nitride raw material under high pressure, a fine-grained, coarse-grained and layered cubic boron nitride polycrystalline structure is formed. The fine-grained crystal particle size is 10-60nm and the coarse-grained crystal particle size is 10-60nm. 100-250 nm, the maximum length of the layered crystal is less than 1000 nm, and the total average particle size is less than 80 nm, which improves the Nu's hardness and Young's modulus.
The nuth hardness of cubic boron nitride polycrystals reaches more than 60GPa and the Young's modulus reaches more than 1082GPa, which significantly improves the hardness and elastic deformation resistance of the material.
Smart Images

Figure CN119177496A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a cubic boron nitride polycrystal used in cutting tools, grinding tools, etc. requiring high hardness and high Young's modulus, and a method for producing the same. Background Art
[0002] Boron nitride (BN) mainly includes three types of boron nitride with different crystal structures: hexagonal BN (hBN), wurtzite BN (wBN) and cubic BN (cBN). Among these BN, cBN has the following advantages: it has a hardness second only to diamond, and its thermal and chemical stability are better than diamond. In particular, compared with diamond, which easily reacts with elements such as iron, nickel, and titanium, cBN is not easy to react with these elements, so it is suitable as a material for tools for processing many materials such as steel materials, nickel alloys, and titanium alloys containing these elements.
[0003] Patent document 1 describes that a raw material powder including a hBN coarse-grained powder having an average particle size of 1 μm or more and a hBN fine-grained powder having an average particle size of less than 100 nm or a powder of BN other than hBN such as amorphous BN is sintered at a temperature of 2200°C or less and a pressure of 25 GPa or less, and the temperature and pressure satisfy a predetermined inequality, thereby producing a polycrystal containing cBN. The cBN polycrystal contains cBN of fine-grained crystals having a maximum particle size of 100 nm or less and an average particle size of 70 nm or less, cBN of plate-like crystals having an average major diameter of 50 nm or more and 10000 nm or less, and cBN of coarse-grained crystals having a minimum particle size of more than 100 nm and an average particle size of 1000 nm or less.
[0004] On the other hand, non-patent document 1 describes that thermally decomposed boron nitride (pBN) which is high-purity BN produced by CVD and has the same hexagonal crystal structure as hBN is transformed into cBN under the conditions of pressure of 25 GPa and temperature of 1950°C, thereby producing a cBN polycrystal in which relatively coarse grains are mixed in a fine polycrystalline structure with an average grain size of about 85 nm.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2016-141609
[0008] Non-patent literature
[0009] Non-patent document 1: Yoshio Ichida and five others, "Microstructure and Mechanical Properties of Nanopolycrystalline cBN", Summary of Lectures at the 60th High Pressure Symposium, Japan Society of High Pressure Research, p. 157, October 10, 2019 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] If the cutting tool or grinding tool is elastically deformed during processing, the processing accuracy is reduced. Therefore, for the materials used in these tools, not only high hardness is required, but also the characteristic of not being easy to produce elastic deformation is required. For this reason, it is necessary to improve the Young's modulus as an indicator indicating that it is not easy to produce elastic deformation. The Young's modulus of the obtained cBN polycrystal is not recorded in patent document 1. The Knoop hardness of the obtained cBN polycrystal is recorded in non-patent document 1 as 55.2GPa and the Young's modulus is 1081.5GPa, but a cBN polycrystal with a Knoop hardness equal to or higher than that and a higher Young's modulus is required.
[0012] An object of the present invention is to provide a cBN polycrystal having a high Knoop hardness and a high Young's modulus, and a method for producing the same.
[0013] Solutions for solving problems
[0014] The cubic boron nitride polycrystal (cBN polycrystal) of the present invention for solving the above-mentioned problems is characterized in that the following crystals are mixed:
[0015] Fine-grained crystals, which are formed of cubic boron nitride and have a particle size in the range of 10 to 60 nm;
[0016] Coarse-grained crystals formed of cubic boron nitride, with a grain size ranging from 100 to 250 nm; and
[0017] A layered crystal, which is formed by stacking a plurality of plate-like crystals formed by cubic boron nitride, wherein the maximum length in a direction perpendicular to the stacking direction is less than 1000 nm, and the aspect ratio obtained by dividing the maximum length by the maximum length (thickness) in the stacking direction is less than 3,
[0018] The average particle size of the fine-grained crystals, the coarse-grained crystals and the layered crystals in total is 80 nm or less.
[0019] Here, the average particle size of fine-grained crystals, coarse-grained crystals and layered crystals refers to the value obtained by the cutting method using a transmission electron microscope (TEM) image based on JIS G0551:2013 (Steel-Microscope Test Method for Crystal Grain Size). In the cutting method, a circle is drawn on the TEM image, and 6 straight lines (diameters) passing through the center of the circle are drawn at 30° intervals (12 for the radius), and the number of grains crossing each straight line (the total count of fine-grained crystals, coarse-grained crystals and layered crystals in the present invention) is counted (wherein, the number of grains counted when the end of the straight line is in the grain is 0.5), and the sum of all straight lines of the number is obtained (the value of the sum is set to "number of grains"). Then, the value obtained by dividing 6 times the diameter by the number of grains is set as the average particle size. It should be noted that the diameter of the circle drawn in the TEM image is not limited to a specific value, and it is preferably specified in a manner that the number of grains in one diameter is about 10 to 40. Preferably, TEM images of a plurality of locations are obtained for one cBN polycrystal, and the average grain size is calculated as the average value of the images of the plurality of locations.
[0020] The particle size d of each fine-grained crystal and coarse-grained crystal can be calculated as follows: approximate the shape of each crystal in the TEM image with an ellipse, measure the major diameter a and minor diameter b of the ellipse on the TEM image, and then calculate the particle size d by approximating it by d=(a+b) / 2. Alternatively, the major diameter a and minor diameter b of the ellipse can be measured by the same method, and the area S of the ellipse can be calculated by S=π×a×b, and the equivalent circle diameter is set as the particle size d, and the area S of the ellipse can be calculated by d=2×(S / π). 1 / 2 In addition, in some cases, commercially available image processing software automatically performs processing for determining the equivalent circle diameter after specifying the outer periphery of a crystal grain included in an image, and therefore the equivalent circle diameter determined from a TEM image using such image processing software may be specified as the grain size d.
[0021] The cBN polycrystal of the present invention can have a Knoop hardness of 60 GPa or more and a Young's modulus of 1082 GPa or more by virtue of the presence of a mixture of fine-grained crystals, lamellar crystals, and coarse-grained crystals of cBN.
[0022] The total average particle size of the fine-grained crystals, the coarse-grained crystals, and the lamellar crystals is preferably 60 nm or less. This can further increase the Knoop hardness and the Young's modulus.
[0023] The cBN polycrystal of the present invention can be manufactured by the following method. That is, the manufacturing method of cubic boron nitride polycrystal (cBN polycrystal) of the present invention is characterized in that a raw material composed of hexagonal boron nitride is heated to a first temperature in the range of 1300 to 1600° C. under a pressure of 10 GPa or more and maintained for a first predetermined time, then heated to a second temperature in the range of 1700 to 2100° C. and maintained for a second predetermined time, and then cooled.
[0024] Here, the “hexagonal boron nitride” as a raw material includes the above-mentioned hBN and pBN.
[0025] In the manufacturing method of cBN polycrystal of the present invention, by heating the above raw materials at a pressure of more than 10GPa and at a first temperature, most of the raw materials are converted into granular crystals of cBN through a diffusion-type phase transformation of hBN, and the remaining raw materials are mainly converted into layered crystals of wBN through a diffusion-free phase transformation (martensitic phase transformation), thereby converting into a crystalline structure in which these granular crystals of cBN and layered crystals of wBN are mixed. Furthermore, in the first prescribed time, a part of the layered crystals of wBN are converted into layered crystals of cBN, and most of the remaining ones maintain the form of layered crystals of wBN. Among them, the layered crystals of wBN are crushed and refined because they are mixed with granular crystals of cBN and layered crystals of cBN that are harder than them under ultra-high pressure during the first prescribed time.
[0026] If the crystal structure in which the granular crystals of cBN, the layered crystals of cBN and the layered crystals of wBN that have been refined are mixed is heated to the second temperature, most of the layered crystals of wBN that have been refined are transformed into layered crystals of cBN through martensitic transformation. Just after the temperature is raised to the second temperature, some layered crystals of wBN remain, and they are all transformed into layered crystals of cBN within the second specified time. As a result, a single-phase cBN polycrystal is formed as a whole. There are a lot of lattice defects such as twins and stacking faults on the surface and inside of these layered crystals of cBN, which are the main reasons for improving the hardness and Young's modulus of the polycrystal.
[0027] In addition, as the heating time at the second temperature passes, new nuclei of cBN are formed around dangling bonds near such lattice defects, and recrystallization toward new grain growth occurs under ultra-high pressure, thereby forming fine-grained crystals of cBN. This is dynamic recrystallization, and many deformations and defects are also introduced into the fine-grained crystals of cBN, which is the main reason for improving the hardness and Young's modulus of the polycrystal. A part of the layered crystals of cBN will not produce such dynamic recrystallization, and remain in a state of maintaining its morphology and improving the hardness and Young's modulus of the polycrystal. On the other hand, the granular cBN crystals generated by heating at the first temperature gradually undergo grain growth as the temperature rises to the second temperature and the holding time passes, and are transformed into coarse-grained crystals of cBN. Since this is also grain growth under ultra-high pressure, there are also many lattice deformations and defects in the coarse-grained crystals of cBN, which is the main reason for improving the hardness and Young's modulus of the polycrystal. Through the above process, the cBN polycrystal of the present invention in which three types of crystals, namely, fine-grained crystals of cBN, lamellar crystals of cBN, and coarse-grained crystals of cBN, are mixed is obtained.
[0028] However, if the heating time at the second temperature is too short, part of the layered crystals of wBN will not be transformed into layered crystals of cBN and will remain. On the other hand, if the heating time at the second temperature is too long, all the layered crystals will be recrystallized and disappear, and the generated fine-grained crystals will become coarse-grained. The previously coarse-grained crystals will also be further coarsened, and the overall structure of the cBN polycrystal will become coarser. Therefore, the second specified time is specified by conducting a preliminary experiment in such a way that the layered crystals of wBN will not remain, and the fine-grained crystals, coarse-grained crystals and layered crystals of cBN will all remain. The existence ratio of fine-grained crystals, coarse-grained crystals and layered crystals is preferably in the range of (13 to 20): (60 to 75): (10 to 30) in terms of area ratio. According to the experiments of the inventors of the present application, if, for example, the pressure is in the range of 10 to 25 GPa, the second temperature is in the range of 1700 to 1950°C, and the second specified time is in the range of 4 to 7 minutes, no layered crystals of wBN will remain, and fine-grained crystals, coarse-grained crystals and layered crystals can all remain, and the Knoop hardness can be set to above 60 GPa and the Young's modulus can be set to above 1082 GPa.
[0029] In addition, if the first specified time is too long, the ratio of the phase transition from the layered crystals of wBN to the layered crystals of cBN increases during the heating at the first temperature, and the layered crystals of wBN are difficult to remain, so it is difficult to produce the miniaturization achieved by the crushing of the layered crystals of wBN. As a result, after the subsequent heating at the second temperature, coarse layered crystals of cBN with an aspect ratio of more than 3 are produced. If so, the structure of the cBN polycrystal becomes coarse as a whole, so a sufficiently high Knoop hardness cannot be obtained. Therefore, the first specified time is also specified in a manner such that the Knoop hardness exceeds 60 GPa through preliminary experiments.
[0030] Effects of the Invention
[0031] According to the present invention, it is possible to obtain a cubic boron nitride polycrystal (cBN polycrystal) having a high Knoop hardness of 60 GPa and a high Young's modulus of 1082 GPa or more. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A flow chart showing one embodiment of a method for producing a cBN polycrystal according to the present invention.
[0033] Figure 2 A diagram showing the relationship between heating temperature and time in the method for producing a cBN polycrystalline body according to the present embodiment.
[0034] Figure 3 A diagram schematically showing a cBN polycrystal according to the present embodiment.
[0035] Figure 4 This is a transmission electron microscope (TEM) photograph of an example of the cBN polycrystal according to the present embodiment.
[0036] Figure 5A A diagram showing the results of X-ray diffraction measurement of a sample obtained by rapid cooling after heat treatment at a first temperature for a first time (without heat treatment at a second temperature).
[0037] Figure 5B Indicates that Figure 4 The graph shown is a result of X-ray diffraction measurement of cBN polycrystal.
[0038] Fig. 6A This is a high-resolution transmission electron microscope (HR-TEM) photograph of a layered crystal, which is an example of a cBN polycrystal according to the present embodiment, taken under magnification.
[0039] Figure 6B This is a HR-TEM photograph of a layered crystal further magnified as an example of the cBN polycrystal according to the present embodiment.
[0040] Figure 7A schematic diagram showing a process of obtaining a cBN polycrystal according to the present embodiment.
[0041] Figure 8 A graph showing the relationship between the second time t2 during production and the measured value of the Knoop hardness of the produced cBN polycrystal.
[0042] Fig. 9 A diagram showing the relationship between the second time t2 during production and the measured value of the Young's modulus of the produced cBN polycrystal.
[0043] Description of Reference Numerals
[0044] 10…Cubic boron nitride (cBN) polycrystal
[0045] 11…(cBN) fine-grained crystals
[0046] 12…(cBN) coarse grained crystal
[0047] 13…Layered crystals (cBN)
[0048] 92…cBN granular crystal
[0049] 93…wBN layered crystals
[0050] SF…Stacking Fault
[0051] T…Twin
[0052] TB…Twin Boundary
[0053] TT…Distance DETAILED DESCRIPTION
[0054] use Figures 1 to 9 Embodiments of the cBN polycrystal and the method for producing the same according to the present invention will be described.
[0055] First, refer to Figure 1 Flowchart and Figure 2 The method for producing the cBN polycrystal according to the present embodiment is described with reference to the drawings.
[0056] First, as a raw material, hexagonal boron nitride (BN) is prepared (step 1). Hexagonal BN can use hBN or pBN. In the examples and comparative examples described below, pBN uses commercially available plate-like pBN (plate thickness 3mm) cut into a disk shape of 3mm in diameter × 3mm in height using a laser processing device, and hBN uses a granular raw material of 3mm in diameter × 3mm in height obtained by filling powdered hBN into a superhard mold for powder molding with an inner diameter of 3mm and pressing it with a powder molding machine at a pressure of 200MPa.
[0057] A pressure P of more than 10 GPa is applied to this raw material (step 2). There is no upper limit to the pressure P. While maintaining the pressure P, the temperature is raised from room temperature to a first temperature (first temperature) T1 in the range of 1300 to 1600°C, preferably in the range of 1350 to 1500°C (step 3). The heating rate is preferably in the range of 50 to 120°C / minute. Next, the first temperature T1 is maintained for a first prescribed time (first time) t1 while maintaining the pressure P (step 4). The first time t1 is appropriately determined together with the second prescribed time (second time) t2 described later through preliminary experiments.
[0058] After the first time t1, the temperature is raised from the first temperature T1 to a second temperature (second temperature) T2 in the range of 1700 to 2100°C, preferably in the range of 1700 to 1950°C, while maintaining the pressure P (step 5). At this time, it is also preferred that the heating rate is in the range of 50 to 120°C / minute. Next, the second temperature T2 is maintained for a second predetermined time (second time) t2 while maintaining the pressure P (step 6). After the second time t2, the temperature is lowered to room temperature, and then the pressure P is reduced to normal pressure (step 7), thereby obtaining the cBN polycrystal of this embodiment.
[0059] Figure 3 The cBN polycrystal 10 of the present embodiment is schematically shown. In the cBN polycrystal 10, fine-grained crystals 11, coarse-grained crystals 12, and layered crystals 13 formed of cBN are all mixed. The particle size of the fine-grained crystals 11 is in the range of 10 to 60 nm, and the particle size of the coarse-grained crystals 12 is in the range of 100 to 250 nm. The layered crystals 13 are formed by stacking a plurality of sheet-like crystals. With respect to the size of the layered crystals 13, the maximum length in the direction perpendicular to the stacking direction of the sheet-like crystals is less than 1000 nm, and the value obtained by dividing the maximum length in this direction by the thickness as the maximum length in the stacking direction (aspect ratio) is less than 3. Since the thickness of each sheet-like crystal is about several nm to 10 nm, having an aspect ratio of less than 3 means that one layered crystal 13 is formed by stacking a plurality of sheet-like crystals.
[0060] Figure 4 The following is a transmission electron microscope (TEM) photograph of an example (Example 1) of the cBN polycrystal 10 of the present embodiment produced by the above method. In Example 1, the above-mentioned pBN was used as a raw material, and the cBN polycrystal 10 was produced under the following conditions: pressure P = 25 GPa, first temperature T1 = 1450°C, first time t1 = 10 minutes, second temperature T2 = 1950°C, and second time t2 = 5 minutes. Figure 4As shown, in the obtained cBN polycrystal 10, fine-grained crystals 11, coarse-grained crystals 12 and layered crystals 13 are mixed. For this sample, the existence ratio of fine-grained crystals 11, coarse-grained crystals 12 and layered crystals 13 is 64:15:21 in terms of area ratio. In addition, the average particle size of the fine-grained crystals 11, coarse-grained crystals 12 and layered crystals 13 was calculated, and the result was 46.3nm.
[0061] The X-ray diffraction measurement of the cBN polycrystal 10 of Example 1 using CuKα rays (wavelength 15.4 nm) obtained the following results: Figure 5B At the same time, for comparison, the results of X-ray diffraction measurement of a sample obtained by rapid cooling after heat treatment at the first temperature T1 for the first time t1 (without heat treatment at the second temperature) at an intermediate stage during the production of the cBN polycrystal corresponding to Example 1 are as follows: Figure 5A shown. Figure 5A In addition to the peaks derived from cBN, peaks derived from wBN are also found. Figure 5B No peak derived from wBN was found, and the cBN polycrystal 10 of Example 1 was confirmed to be a single-phase cBN polycrystal.
[0062] In order to investigate the structure of the layered crystal 13 in further detail, Figure 4 The HR-TEM (high-resolution transmission electron microscope) photographs of the cBN polycrystal 10 and a portion of the layered crystal 13 are shown in FIG. Fig. 6A As shown, the HR-TEM photo obtained by further enlarging it is as follows Figure 6B As shown in these photos, we can see how multiple plate-like crystals are stacked. In particular, Figure 6B It is shown that within the layered crystal 13, the plate-like crystals are stacked with crystal planes {111}, and these crystal planes are used as twin boundaries TB to form many twins T. The distance TT between the twin boundaries TB is less than 10nm. In addition, a plurality of stacking faults SF are formed within the layered crystal 13. It is believed that the presence of these twins T and stacking faults SF in the layered crystal 13 is one of the main reasons for the increase in the Knoop hardness and Young's modulus of the cBN polycrystal 10. In addition, these twins T and stacking faults SF also have the effect of hindering the progress of cracks in the cBN polycrystal 10.
[0063] The Knoop hardness and Young's modulus of the cBN polycrystal 10 of Example 1 were measured, and the results showed that the Knoop hardness was 65.6 GPa and the Young's modulus was 1085.7 GPa. Thus, the cBN polycrystal 10 of Example 1 had a high Knoop hardness of 60 GPa and a higher Young's modulus of 1082 GPa or more than that of conventional cBN polycrystals.
[0064] The process of forming the cBN polycrystalline 10 uses Figure 7 First, when a raw material composed of hexagonal BN is heated to a first temperature T1 under a pressure of 10 GPa or more, granular crystals 92 of cBN and layered crystals 93 of wBN are formed ( Figure 7 ). If the first temperature T1 is maintained for the first time t1, a portion of the wBN layered crystals 93 is transformed into cBN layered crystals 13 ( Figure 7 The remaining wBN layered crystals 93 are then crushed and refined by the hard cBN layered crystals 13 and granular crystals 92 under high pressure. If the temperature is raised from the first temperature T1 to the second temperature T2, a phase transition ( T1 ) occurs from the refined wBN layered crystals 93 to the cBN layered crystals 13. Figure 7 ), during the second time t2 maintained at the second temperature T2, the layered crystals 93 of wBN are all transformed into the layered crystals 13 of cBN ( Figure 7 (left middle figure). During the second time t2 at the second temperature T2, a new cBN nucleus is formed in a part of the cBN layered crystal 13, starting from a dangling bond near a lattice defect, and dynamic recrystallization occurs, which grows into a new fine cBN crystal. As a result, a part of the cBN layered crystal 13 is transformed into a cBN fine crystal 11 ( Figure 7 In this way, a cBN polycrystal 10 in which fine-grained cBN crystals 11, coarse-grained cBN crystals 12, and layered cBN crystals 13 are mixed is obtained. Here, if the second time t2 is too short, part of the layered wBN crystals 93 remain, so the second time t2 is set in such a way that all the layered wBN crystals 93 are transformed into the layered cBN crystals 13.
[0065] If the heating at the second temperature T2 is continued after the second time t2 has passed, all the cBN layered crystals 13 are transformed into cBN fine crystals 13 by dynamic recrystallization and disappear, and the cBN fine crystals 13 formed before and after the second time t2 have passed undergo grain growth and become coarser ( Figure 7 ). If so, the cBN polycrystal 10 of the present embodiment having high Knoop hardness and Young's modulus cannot be obtained. Therefore, the second time t2 needs to be set in such a way that the cBN fine crystals 11 and the cBN layered crystals 13 remain.
[0066] In the preliminary experiment when the conditions of the second time t2 described here are specified, it is sufficient to confirm the formed crystals by using TEM photos for multiple samples prepared at different second times t2, or to confirm whether wBN remains by using X-ray diffraction measurement. Alternatively, it is also possible to measure the Knoop hardness and Young's modulus for multiple samples prepared in the same way, and if they are 60 GPa or more and 1082 GPa or more, it is presumed that the conditions of each crystal are met.
[0067] Next, cBN polycrystal 10 was produced under multiple conditions of different first temperature and first time, second temperature and second time, and pressure, and the average grain size, the existence ratio (area ratio) of fine grain crystal 11, coarse grain crystal 12 and lamellar crystal 13, Knoop hardness and Young's modulus were measured (Examples 2 to 8). At the same time, the same measurement was also performed on Comparative Examples 1 and 2 in which the second time was longer than that of Examples 1 to 7. Furthermore, the same measurement was also performed on Comparative Examples 3 to 7 produced by heating from room temperature to a predetermined temperature and maintaining the temperature for a predetermined time without performing two-stage heating at the first temperature and the second temperature. The production conditions and measurement results of the samples of Examples 1 to 8 and Comparative Examples 1 to 7, including the aforementioned Example 1, are shown in Table 1. It should be noted that in Comparative Examples 3 to 7, for convenience, the heating temperature and the time maintained at the temperature are recorded in the columns of the first temperature and the first time, but they are not equivalent to the first temperature and the first time in the present invention.
[0068] [Table 1]
[0069]
[0070] For the samples of Examples 1 to 8, the average particle size is 80 nm or less, and all of them have fine-grained crystals 11, coarse-grained crystals 12, and layered crystals 13, and none of them has medium-grained crystals. The samples of Examples 1 to 8 all have a high value of Knoop hardness of 60 GPa or more, and a high value of Young's modulus of 1082 GPa or more. In contrast, in Comparative Examples 1 to 7, layered crystals 13 do not exist, or exist only at a low ratio of 5% or less in terms of area ratio, which can be ignored. In particular, in Comparative Examples 1 and 2, although two-stage heating at the first temperature and the second temperature is performed in the same manner as in Examples 1 to 8, the second time is longer than in Examples 1 to 8 (4 to 6 minutes in Examples 1 to 8, 10 to 15 minutes in Comparative Examples 1 and 2), so that layered crystals 13 do not exist or are reduced to a negligible degree, so both Knoop hardness and Young's modulus are reduced compared to Examples 1 to 8.
[0071] Next, the Knoop hardness ( Figure 8 ) and Young's modulus ( Fig. 9 )’s measurement results. Figure 8 and Fig. 9 Also shown are samples that were maintained at the first temperature (1450°C) for a specified period of time and then cooled to room temperature without heating; samples that were immediately cooled after reaching the second temperature (the second time was 0); and a comparative example that was heated from room temperature to 1950°C and maintained at this temperature for a specified period of time without performing two-stage heating at the first and second temperatures. Figure 8 and Fig. 9 It is found that when the second time is between 4 and 7 minutes, the Knoop hardness can be set to 60 GPa or more, and the Young's modulus can be set to 1082 GPa or more.
[0072] The cBN polycrystal 10 obtained in this embodiment has the following characteristics: it has high Knoop hardness and Young's modulus, and can be suitably used as a material for cutting edges of cutting tools and abrasive grains of grinding tools. In addition, the cBN polycrystal 10 can also be suitably used as an indenter for hardness measurement.
Claims
1. A cubic boron nitride polycrystal, characterized in that: The following crystals are mixed: Fine-grained crystals, which are formed of cubic boron nitride and have a particle size in the range of 10 to 60 nm; Coarse-grained crystals, which are formed of cubic boron nitride and have a particle size in the range of 100 to 250 nm; and A layered crystal, which is formed by stacking a plurality of plate-like crystals formed by cubic boron nitride, wherein the maximum length in a direction perpendicular to the stacking direction is less than 1000 nm, and the aspect ratio obtained by dividing the maximum length by the maximum length in the stacking direction is less than 3, The existence ratio of the fine-grained crystals, the coarse-grained crystals and the lamellar crystals is in the range of (13 to 20): (60 to 75): (10 to 30) in terms of area ratio, The average particle size of the fine-grained crystals, the coarse-grained crystals and the layered crystals in total is 80 nm or less.
2. The cubic boron nitride polycrystal according to claim 1, characterized in that: The average particle size of the fine-grained crystals, the coarse-grained crystals, and the layered crystals in total is 60 nm or less.
3. A method for producing cubic boron nitride polycrystals, characterized in that: The method is a method for producing the cubic boron nitride polycrystal according to claim 1 or 2, A raw material formed of hexagonal boron nitride is heated to a first temperature in the range of 1300-1600°C under a pressure of 10 GPa or more and maintained for a first predetermined time, then heated to a second temperature in the range of 1700-2100°C and maintained for a second predetermined time, and then cooled.
4. A cutting tool, characterized in that: It has a cutting edge formed of the cubic boron nitride polycrystal according to claim 1 or 2.
5. A grinding tool, characterized in that: The invention comprises abrasive grains formed of the cubic boron nitride polycrystal according to claim 1 or 2.
6. A hardness measuring indenter, characterized in that: It is formed of the cubic boron nitride polycrystal according to claim 1 or 2.
Citation Information
Patent Citations
Cubic boron nitride composite polycrystal, production method thereof, and cutting tool, abrasion resistance tool and grinding tool each equipped with the cubic boron nitride composite polycrystal
JP2014080321A
Cubic boron nitride composite polycrystal, production method thereof, and cutting tool, abrasion resistance tool and grinding tool each equipped with the cubic boron nitride composite polycrystal
JP2014080323A
Cubic boron nitride polycrystalline material, cutting tool, wear resistant tool, grinding tool, and method of manufacturing cubic boron nitride polycrystalline material
US20180265416A1
Polycrystalline cubic boron nitride and method for manufacturing the same
US20200247673A1
Cubic boron nitride polycrystalline body and method for producing same, and cutting tool and grinding tool
WO2018088369A1
